THE EFFECT OF COMPENSATION, WORK DISCIPLINE, AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE AGENCY OF STATISTICS CENTER OF SOUTH ACEH - Febyolla Presilawati; Mimiasri Mimiasri; Zuhri Kurniawan Khalid; M. Dharma Nauval (Universitas Muhammadiyah Metro, 2022)
This study aims to determine: the effect of compensation on the performance of the Central Bureau of Statistics of South Aceh Regency, the effect of work discipline on the performance of the Central Bureau of Statistics of South Aceh Regency, the effect of career development on the performance of the Central Bureau of Statistics of South Aceh Regency and the effect of compensation, work discipline and career development has a significant effect on the performance of the Central Bureau of Statistics of South Aceh Regency. The sample used in this study were 40 employees. The analytical technique used is multiple linear regression analysis using the F hypothesis test and the t hypothesis test with a significant level of 5%. The test results prove that compensation and work discipline have a simultaneous and partial effect on the performance of BPS employees in South Aceh Regency, while employee career development has a simultaneous but not partial effect